2011
DOI: 10.1093/cercor/bhr027
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Coding of Traits and States in the Perception of Pain

Abstract: Perception is not a simple reflection of sensory information but varies within and between individuals. This applies particularly to the perception of pain, which, in the brain, is associated with neuronal responses at different frequencies. Here, we show how these different neuronal responses subserve interindividual and intraindividual variations in the perception of identical painful stimuli. A time-frequency analysis of single trial electroencephalographic data indicates that pain-related responses in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
88
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 41 publications
15
88
0
1
Order By: Relevance
“…A recent study in mice has shown that theta waves are present in the ACC during fear learning (Jeon et al 2010). These signals are also involved in pain physical perception (Liu et al 2010;Schulz et al 2011) and in empathy for pain in humans (Mu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in mice has shown that theta waves are present in the ACC during fear learning (Jeon et al 2010). These signals are also involved in pain physical perception (Liu et al 2010;Schulz et al 2011) and in empathy for pain in humans (Mu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that exclusion periods would trigger low cerebral waves, that is, waves located in the theta band frequency. Theta signals, compared with more cognitive cerebral waves such as gamma or beta (Buzsaki 2002), are known to be associated with emotional feelings and primitive sensations (Knyazev 2007), physical pain (Liu et al 2010;Schulz et al 2011), and empathy for pain (Jeon et al 2010). The observation that theta oscillations play an important role in human emotional processing has been widely documented by electroencephalography studies during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, laser-induced gamma-band oscillations have been observed at a latency of ϳ200 ms after stimulus onset, within a frequency range of 50 to 100 Hz (Gross et al, 2007;Tiemann et al, 2010). A 200 ms Hanning window is appropriate for identifying these responses, as (1) it provides a sufficiently high frequency resolution of 5 Hz, (2) it is adequate to avoid contamination of the estimates of poststimulus EEG responses by prestimulus activity, (3) it is in line with the duration of GBOs described by Gross et al (2007) and Schulz et al (2011b).…”
Section: Eeg Data Analysismentioning
confidence: 97%
“…Recently, using electroencephalography and magnetoencephalography (MEG), it has been reported that also nociceptive stimuli elicit gamma-band oscillations (GBOs) within the human primary somatosensory cortex (SI; Gross et al, 2007;Hauck et al, 2007). Because the magnitude of these GBOs correlates with the subjective pain intensity, it has been suggested that they reflect cortical activity related directly to the perception of pain (Gross et al, 2007;Schulz et al, 2011b). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation